Fructose intake during gestation and lactation differentially affects the expression of hippocampal neurosteroidogenic enzymes in rat offspring. (2nd January 2017) - Mizuno, Genki; Munetsuna, Eiji; Yamada, Hiroya; Ando, Yoshitaka; Yamazaki, Mirai; Murase, Yuri; Kondo, Kanako; Ishikawa, Hiroaki; Teradaira, Ryoji; Suzuki, Koji; Ohashi, Koji
ABSTRACT: Neurosteroids, steroidal hormones synthesized de novo from cholesterol within the brain, stimulate hippocampal functions such as neuron protection and synapse formation. Previously, we examined the effect of maternal fructose on the transcriptional regulation of neurosteroidogenic enzymes. We found that the mRNA expression level of the steroidogenic acute regulatory protein (StAR), peripheral benzodiazepine receptor (PBR), cytochrome P450(11β), 11β-hydroxysteroid dehydrogenase (HSD), and 17β-HSD was altered. However, we could not determine whether maternal fructose intake played a role in the gestation or lactation period because the dam rats were fed fructose solution during both periods. Thus, in this study, we analyzed the hippocampi of the offspring of dams fed fructose during the gestation or lactation period. Maternal fructose consumption during either the gestation or lactation period did not affect the mRNA levels of StAR, P450(17α), 11β-HSD-2, and 17β-HSD-1. PBR expression was down-regulated, even when rats consumed fructose during the lactation period only, while fructose consumption during gestation tended to activate the expression of P450(11β)-2. We found that maternal fructose intake during gestation and lactation differentially affected the expression of hippocampal neurosteroidogenic enzymes in the offspring.